PY-RATE ADVENTURES: A 2D Platform Serious Game for Learning the Basic Concepts of Programming With Python - Sideris, Grigorios; Xinogalos, Stelios (Simulation & gaming, 2019)
Background. Learning programming is a cognitively demanding field of study accompanied with various difficulties. Although there is a high demand in the market for programmers, software analysts and engineers, a high dropout rate is recorded in relevant fields of study. Serious games are a promising means of engaging students in learning programming by giving them more incentives and making the process of learning programming concepts and languages more entertaining. Aim. This article introduces a new serious game called PY-RATE ADVENTURES, which aims to assist young students in their introduction to the basic programming concepts using Python. The game does not have any prerequisites and is suitable for players with no previous knowledge of programming. This article aims to present important information regarding the analysis, design and pilot evaluation of PY-RATE ADVENTURES. Method. The game was evaluated by 31 people that had recently graduated or were students of an Interdepartmental Programme of Postgraduate Studies in Information Systems. The participants voluntarily played the game and answered a questionnaire based on the MEEGA+ model, after their hands on experience with the game. This questionnaire’s purpose was to evaluate PY-RATE ADVENTURES in terms of perceived player experience and short-term learning. Results. The participants positively evaluated the game almost in all the elements of player experience. Furthermore, the majority of the users consider that the game helped them to learn basic programming concepts in Python and stated that they would prefer to learn programming with this game rather than other teaching methods. Conclusion. The positive results of the pilot evaluation give us the motivation to proceed and evaluate the game with students in secondary education, in order to extract stronger and generalisable conclusions regarding the impact of the game as an educational tool for learning programming concepts.